2013
DOI: 10.1111/cei.12127
|View full text |Cite
|
Sign up to set email alerts
|

The significance of pretransplant donor-specific antibodies reactive with intact or denatured human leucocyte antigen in kidney transplantation

Abstract: SummaryAntibodies recognizing denatured human leucocyte antigen (HLA) can co-react with epitopes on intact HLA or recognize cryptic epitopes which are normally unaccessible to HLA antibodies. Their specificity cannot be distinguished by single antigen beads (SAB) alone, as they carry a mixture of intact and denatured HLA. In this study, we selected pretransplant sera containing donor-specific HLA class I antibodies (DSA) according to regular SAB analysis from 156 kidney transplant recipients. These sera were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 21 publications
(29 reference statements)
3
85
0
1
Order By: Relevance
“…In order to facilitate the most accurate comparisons between the models, stepwise regression analysis was originally used but all variables from any model that were significant were ultimately forced into the final models to ensure exact similarity. (3) HLA antibodies detected using Luminexbased assays can react with denatured HLA antigens (32,(43)(44)(45)(46). Previous studies in renal and heart transplantation demonstrated that these antibodies are not clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to facilitate the most accurate comparisons between the models, stepwise regression analysis was originally used but all variables from any model that were significant were ultimately forced into the final models to ensure exact similarity. (3) HLA antibodies detected using Luminexbased assays can react with denatured HLA antigens (32,(43)(44)(45)(46). Previous studies in renal and heart transplantation demonstrated that these antibodies are not clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…This cutoff was utilized because of prior data (18,21,22). Separate testing for denatured class I HLA antigens was not performed (32). The outcomes of patients based on pre-transplant (21) and de novo (22) standard DSA testing have been previously published.…”
Section: Study Populationmentioning
confidence: 99%
“…The literature to date suggests that anti-dHLAs are irrelevant since they are unable to recognize the donor HLA target on the cell surface and therefore have no influence on graft function or survival [14,[21][22][23][24][25]. Consequently, in graft allocation programs, it seems unreasonable to consider the HLA antigens targeted by such antibodies as unacceptable mismatches.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] However, detection of serum DSA with SAFB has technical limitations, falsenegative and false-positive results being respectively caused by complement interference [17][18][19] and by anti-HLA antibodies of ill-defined pathogenic role recognizing denatured class I HLA molecules. [20][21][22][23][24][25] The presence of DSA is not synonymous with lung allograft injury. 26 The lack of direct association may be due to the inability of the DSA to bind to the graft because of the absence of expression of cognate HLA molecules, or because of insufficient binding strength between a low affinity DSA and its target.…”
Section: Introductionmentioning
confidence: 99%